The ghost goes to the dogs - Coyle, Cleo (Kimberly, Alice. Haunted bookshop mystery, 2023)
"Pet Mystery Week brings brisk business to Penelope's Rhode Island bookshop, but a real mystery comes barking at her door when a lost dog turns up in a panic. Pen and her son Spencer follow the furry fugitive to a wooded area where the dog's owner lies unconscious. Mrs. Cunningham is a warm-hearted widow who volunteers at the animal shelter and runs Buy the Book's pet lovers book club. Why would anyone shoot such a sweet soul? The police believe it's an accident, a shot by a careless deer hunter, but Pen remains skeptical. To straighten out this doggone mess, she whistles for the ghost of PI Jack Shepard, an expert in hounding as well as haunting. Jack has a dog story of his own, a case from the 1940s that may help Pen sniff out clues to her present predicament. Yet even with Jack's hard-boiled help, Pen may not be able to stop the killer from striking again or letting this whole case go to the dogs..."--Amazon.